2020
DOI: 10.1037/amp0000592
|View full text |Cite
|
Sign up to set email alerts
|

A developmental framework of binge-eating disorder based on pediatric loss of control eating.

Abstract: Although binge-eating disorder may manifest in childhood, a significantly larger proportion of youth report episodes involving a loss of control while eating, the hallmark feature of binge eating that predicts excess weight gain and obesity. Adults with binge-eating disorder often report that symptoms emerged during childhood or adolescence, suggesting that a developmental perspective of binge eating may be warranted. Thus, loss of control eating may be a marker of prodromal binge-eating disorder among certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 154 publications
(219 reference statements)
2
60
0
1
Order By: Relevance
“…Different theoretical accounts on problematic eating, overweight, and obesity propose that food stimuli automatically attract visual attention, particularly in individuals with overweight and weight concerns (e.g., Appelhans, 2009 ; Berridge, 2009 ; Appelhans et al, 2016 ; Tanofsky-Kraff et al, 2020 ). An attentional preference for food is thought to have been evolutionary adaptive in ancient times since it facilitated finding scarce food in the harsh environment, allowing food intake whenever possible, and thus increasing chances for survival.…”
Section: Introductionmentioning
confidence: 99%
“…Different theoretical accounts on problematic eating, overweight, and obesity propose that food stimuli automatically attract visual attention, particularly in individuals with overweight and weight concerns (e.g., Appelhans, 2009 ; Berridge, 2009 ; Appelhans et al, 2016 ; Tanofsky-Kraff et al, 2020 ). An attentional preference for food is thought to have been evolutionary adaptive in ancient times since it facilitated finding scarce food in the harsh environment, allowing food intake whenever possible, and thus increasing chances for survival.…”
Section: Introductionmentioning
confidence: 99%
“…Although physical activity and LOC eating share intriguingly similar developmental timeframes during which significant changes in these behaviors occur, they are almost entirely studied apart from one another. Consistently, recent reviews of the literature on LOC eating in youth did not discuss physical activity as relevant risk factor for LOC eating ( Byrne et al, 2019 ; Tanofsky-Kraff et al, 2020 ). Nevertheless, mounting evidence suggests that higher overall physical activity may exert beneficial effects on eating behavior, and this is supported by studies in adults showing that higher levels of physical activity are related to better appetite regulation, reduced food cue responsivity, and less binge eating ( Joseph et al, 2011 ; Luo et al, 2018 ).…”
Section: Physical Activity and Pediatric Loc Eatingmentioning
confidence: 75%
“…Moreover, the mechanisms underlying associations between physical activity and eating regulation have yet to be elucidated. While several factors have been posited to contribute to these relationships, burgeoning evidence indicates acute and long-term physical activity behavior enhance executive functioning, and poor executive functioning increases risk for the development of LOC eating ( Verburgh et al, 2014 ; Goldschmidt et al, 2015 ; Alvarez-Bueno et al, 2017 ; Tanofsky-Kraff et al, 2020 ). Executive functions refer to “top-down” cognitive processes that guide goal-directed behavior and allow for adaptations to changing circumstances, and which are rooted in circuitry within the prefrontal cortex ( Diamond, 2013 ).…”
Section: Executive Functioning As a Mechanism Linking Activity And Lomentioning
confidence: 99%
“…On the other hand, controlling for BMI eliminated the positive relation between adoption status and W3 binge eating. Given that binge eating tends to predict weight gain and obesity (Tanofsky‐Kraff et al, 2020), we suspect that BMI is more likely functioning as an indicator of binge eating, rather than as a confounding factor. That the same association was no longer significant after controlling for parent education is more puzzling, especially because past research has shown no relationship between parent education and binge eating in children (Saltzman & Liechty, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Diet pill use has been associated with cardiac conditions (e.g., Cahill et al, 2013) and self-induced vomiting has been linked to numerous medical sequelae ranging from mild to severe, including electrolyte imbalance, cardiac arrhythmias, and even death (Brown & Mehler, 2013). Binge eating, even at subthreshold levels, may predict weight gain and the development of binge-eating disorder, which increases the risk for metabolic syndrome and other health conditions (Tanofsky-Kraff, Schvey, & Grilo, 2020). The risks associated with these behaviors suggest that parents and clinicians working with adopted individuals should be attentive to identifying and addressing eating and weight control behaviors.…”
Section: Discussionmentioning
confidence: 99%